تابعية مكونات المساحيق النانوية لأكاسيد الألمنيوم والحديد المتشتتة لدرجة حرارة الشعلة الغازية الطبقية - سعد علي (Latakia University Journal -Basic Sciences Series, 2018)
تعتمد التقنية المستخدمة في العمل على تركيب تشتتي لمزيج غازي مستعلق لمسحوق مادة العيّنة يحترق في وسط مؤكسد للحصول على خلائط ومساحيق جديدة تحتوي على جسيمات عالية التشتت وذلك بطريقتين:الأولى بتقديم المزيج المخلوط مسبقا مع المؤكسد إلى منطقة الاحتراق. الثانية بمزج العناصر المختلفة في الوقت نفسه مع بدء عملية الاحتراق. بتحليل نواتج الاحتراق لأكسيد الألمنيوم تبيّن أن هناك نموذجين بحسب الحجم: الأول الأكثر نعومة ويشكل 10%،والثاني قليل التشتت ويشكل 90% وتزداد حتى 97% بزيادة الأوكسجين بنسبة 3%.أما في حالة احتراق مسحوق الحديد فكان وفقا لنموذجين بحسب حجم جزيئات مسحوق الحديد: الأول قياس جزيئاته 0.05 وهو عبارة عن الأكسيد التامFe2 O3 والآخر قياس جزيئاته o.8وهو عبارة عن Fe3 O4 . The technique used in this work depends on the scattered installation of a suspension of combination of gas of powder material sample burning in the middle of oxidizer for new alloys and powders containing particles of high scattering. This is done in two ways: first, by providing pre-mixed mixture with the oxidizer to the combustion area; second, by mixing the different elements at the same time with the start of the combustion process. Analysis of combustion products of aluminum oxide shows presence of two forms by size: the first, softer and constitutes 10%; the second, little dispersion, and constitute 90% and increased to 97% oxygen, up by 3%. As for combustion of iron powder, it was done according to two models based on size of particles of iron powder: one, measurement of molecules is . It is a full oxide Fe2 O3, and the other is the measurement of fractions .It is a Fe3 O4.